2006
DOI: 10.1007/s11671-006-9006-8
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate structure of hydroxyproline-rich glycoprotein (HRGP) and HRGP assisted dispersion of carbon nanotubes

Abstract: Hydroxyproline-rich glycoproteins (HRGP) comprise a super-family of extracellular structural glycoproteins whose precise roles in plant cell wall assembly and functioning remain to be elucidated. However, their extended structure and repetitive block co-polymer character of HRGPs may mediate their self-assembly as wall scaffolds by like-with-like alignment of their hydrophobic peptide and hydrophilic glycopeptide modules. Intermolecular crosslinking further stabilizes the scaffold. Thus the design of HRGP-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The binding enthalpy contributions of X are plotted as a function of the Kyte-Doolittle hydropathy index in Figure , where a decrease in hydropathy is associated with stronger binding. These results are consistent with numerous studies on peptide surface interactions on several points. ,,, First, the phenomenon of protein adsorption is known to occur on hydrophobic surfaces . Second, solvent effects have been shown to play a major role in protein adsorption due to the water structure at the biomaterial interface. , Further, many experimental studies have determined that hydrophilic molecules bind to graphitic surfaces. ,,, Finally, experimental evidence exists demonstrating that hydrophilic proteins bind to graphitic surfaces more readily than hydrophobic proteins …”
Section: Resultssupporting
confidence: 85%
“…The binding enthalpy contributions of X are plotted as a function of the Kyte-Doolittle hydropathy index in Figure , where a decrease in hydropathy is associated with stronger binding. These results are consistent with numerous studies on peptide surface interactions on several points. ,,, First, the phenomenon of protein adsorption is known to occur on hydrophobic surfaces . Second, solvent effects have been shown to play a major role in protein adsorption due to the water structure at the biomaterial interface. , Further, many experimental studies have determined that hydrophilic molecules bind to graphitic surfaces. ,,, Finally, experimental evidence exists demonstrating that hydrophilic proteins bind to graphitic surfaces more readily than hydrophobic proteins …”
Section: Resultssupporting
confidence: 85%
“…Cell surfaces may collide with SWCNTs millions of times during incubation. It has been reported that glycoproteins can disperse SWCNTs in aqueous solutions, 45 and SWCNTs also interact strongly with polysaccharides, such as chitosan. 46 Thus, individual nanotubes may adsorb on cell surfaces, and more nanotubes on the cell surface would bundle together owing to the strong van der Waals attractions between nanotubes.…”
Section: Mechanical Properties Of Bacterial Cellsmentioning
confidence: 99%
“…Noncovalent surface functionalization has so far employed various natural biopolymers, such as polysaccharides (Gum Arabic (a highly branched arabinogalactan polysaccharide: 70-80 % arabingalactan, 20 % arabingalactan-protein complex), [7] starch, [8] amylose, [9] glycosylated polymers, [10] schizophyllan and curdlan (b-1,3-glucans), [11] alginic acid, [12] water-soluble chitosan [13] ), peptide, [14] DNA, [15] green tea (catechins), [16] natural lignosulfonate-based polyelectrolytes, [17] artificial conjugate polymers, [18] and pyrene-containing polymers. [19] Many polyaromatic, especially small pyrene-based molecules and ions (electrolytes), have also been used as surface modifiers of carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%